Association of environmental and behavioural factors with cardiovascular disease mortality - Bahadır Açıktepe; Sevval Nil Esirgun; Mehmet Kocak (ESC Heart Failure)
Abstract Aims Recognizing the rising concern of environmental impacts on health, the study aims to explore how specific environmental factors such as air pollution, humidity, and temperature variations contribute to the prevalence of cardiovascular disease (CVD) mortality, emphasizing the role of air quality, climate variables, and lifestyle factors in the disease mortality specifically. Methods and results Analysis of province‐level data on CVD mortality in Turkey from 2010 to 2019, assessing the correlations with environmental and lifestyle factors like particulate matter, sulfur dioxide, meteorological variables, and smoking and alcohol consumption. The study employs the SAS TRAJ procedure and Ordinal Logistic Regression for statistical analysis. The multiplicity correction was done through Benjamini–Hoechberg false discovery rate (FDR) approach. As expected, both smoking and alcohol consumption were found to be significantly associated with CVD mortality (odds ratio (OR): 1.10, 95% CI: 1.08, 1.11, P‐value < 0.0001). While median Air Pressure and Humidity were among the most significant markers with OR of 1.10 indicating an increasing CVD mortality, their variability metrics such as coefficient of variation (CV) showed significant protective effects with OR of 0.37 and 0.89, respectively. Temperature and its variability seemed to be protective overall. Conclusions Our research highlights the significant influence of environmental factors on cardiovascular health, especially air pressure and humidity, beyond the known factors such as smoking and alcohol consumption. These findings suggest the need for comprehensive public health strategies that address both environmental and lifestyle risk factors to effectively reduce the burden of cardiovascular diseases.